METODE PELAKSANAAN OVERLAY REKONSTRUKSI PADA PROYEK CIKOWOAN – KADUT (REGULER) DI STA 1 + 700 s/d STA 2 + 286 - Maulana, Rizky; Kholiq, Abdul (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2023)
In terms of access to mobilization/demobilization and the location is very steep, the dump load is minimal due to poor access. Very high rainfall has resulted in further delays in the implementation of work. ACBC (Asphalt Concrete Binder Course) asphalt foundation and top layer or asphalt surface wear layer ACWC (Asphalt Wearing Course) for the material used, namely Asphalt Emulsion CSS -1 or SS -1 layer thickness (AC-BC) solid with a thickness of 0.6 cm with a loose thickness of 7.4 cm, the layer thickness (AC-WC) was solid with a thickness of 0.5 cm and a loose thickness of 6.4 cm. AC-WC compaction is divided into 3 parts, namely first compaction (breakdown rolling), second compaction (intermediate rolling), final compaction (final rolling). The first compaction is carried out when the temperature reaches 111 C to 102 C or about 0 – 10 minutes from the time the AC – WC is held. This ride uses a tandem roller with the number of tracks according to the trial compaction. The second compaction is carried out at a temperature of 102 C to 83 C or about 10-20 minutes since the AC-WC was held. This event uses a Pneumatic Roller with the number of passes according to trial compaction. The final compaction was carried out at a temperature of 83 C to 63 C or around 20-45 minutes since the AC-WC was held. This event uses a Pneumatic Tandem Roller with 12 to 15 passes. In the work of the Cikowoan – Kadut Road Improvement Reconstruction Project in Majalengka Regency, the tools used are Mini Excavators, Asphalt Tanks and assistive devices (asphalt sprayer), Dump trucks, Tandem combin rollers, Mini iron wheel compactor machines (baby roller), soil compactor machine.